'ND Whitetail', a new white kidney bean with high seed yield and intermediate resistance to white mold and bacterial blights. Issue 2 (14th March 2020) - Osorno, Juan M.; Vander Wal, Albert J.; Posch, John; Simons, Kristin; Grafton, Kenneth F.; Pasche, Julie S.
Abstract: 'ND Whitetail' (Reg. no. CV‐327, PI 690447; PVP‐201900175) is a new white kidney bean cultivar developed by the dry bean breeding program at North Dakota State University and released by the North Dakota Agricultural Experiment Station. Within the Andean gene pool, kidney beans are the most economically important market classes worldwide, with dark‐red kidney bean being the most commonly grown class, followed by light‐red and white kidneys. There is an increased interest in white kidney bean in the United States, mostly stimulated by novel research claiming additional health benefits related to its consumption. However, biotic and abiotic stresses still limit the full seed yield potential of kidney bean cultivars. Averaged across environments, the seed yield of ND Whitetail was significantly higher by 650, 976, and 459 kg ha −1 than 'Beluga', 'Silver Cloud', and 'Snowdon', respectively. ND Whitetail has an average plant height of 52 cm and matures in approximately 101 d. Results from canning tests showed that ND Whitetail received a canning score of 5.1. ND Whitetail has high levels of resistance to white mold and Bean common mosaic virus (BCMV) along with intermediate resistance to bacterial diseases. Given the superior seed yield quality and agronomic performance, useful agronomic traits such as seed size, BCMV resistance, white mold and halo blight resistance, and superior canning quality, ND Whitetail could become an important white kidney cultivar in the United States.